Improving nutritional quality and fungal tolerance in soya bean and grass pea by expressing an oxalate decarboxylase. Issue 6 (22nd January 2016) - Kumar, Vinay; Chattopadhyay, Arnab; Ghosh, Sumit; Irfan, Mohammad; Chakraborty, Niranjan; Chakraborty, Subhra; Datta, Asis
Summary: Soya bean ( Glycine max ) and grass pea ( Lathyrus sativus ) seeds are important sources of dietary proteins; however, they also contain antinutritional metabolite oxalic acid (OA). Excess dietary intake of OA leads to nephrolithiasis due to the formation of calcium oxalate crystals in kidneys. Besides, OA is also a known precursor of β‐ N ‐oxalyl‐L ‐α, β‐diaminopropionic acid (β‐ODAP), a neurotoxin found in grass pea. Here, we report the reduction in OA level in soya bean (up to 73%) and grass pea (up to 75%) seeds by constitutive and/or seed‐specific expression of an oxalate‐degrading enzyme, oxalate decarboxylase (FvOXDC) of Flammulina velutipes . In addition, β‐ODAP level of grass pea seeds was also reduced up to 73%. Reduced OA content was interrelated with the associated increase in seeds micronutrients such as calcium, iron and zinc. Moreover, constitutive expression of FvOXDC led to improved tolerance to the fungal pathogen Sclerotinia sclerotiorum that requires OA during host colonization. Importantly, FvOXDC ‐expressing soya bean and grass pea plants were similar to the wild type with respect to the morphology and photosynthetic rates, and seed protein pool remained unaltered as revealed by the comparative proteomic analysis. Taken together, these results demonstrated improved seed quality and tolerance to the fungal pathogen in two important legume crops, by the expression of an oxalate‐degrading enzyme.